Temporal resolution in fluorescence imaging - Mondal, Partha Pratim (Frontiers in Molecular Biosciences, 2014)
Temporal resolution is a key factor for imaging rapidly occurring events in biology. In this feature article, I investigate an approximate estimate for determining the temporal resolution limit. The condition that led to this limit is, the time taken by the ensemble (99.9 %) of excited molecules to relax to ground state, assuming all the emitted photons are detected. In a simplistic three-level system, the temporal resolution is, ≈ 3τ_p, where τ_p = (\log_e{10})/(k_f +k_{nr}) and, k_f and k_{nr} are respectively the radiative and non-radiative emission rates. This further assumes the ideal condition that, the quantum efficiency of the detector is unity and there are no other loses. We discuss few state-of-art microscopy techniques that are capable of high temporal resolution. This includes techniques such as multifocal multiphoton microscopy (MMM), multifocal plane microscopy, multiple excitation spot optical microscopy (MESO), multiplane microscopy and multiple light-sheet microscopy (MLSM).